Differences of Spermatozoa Concentration Analysis Between Manual and Automatic Methods - Emma Ismawatie; Purwanto Adhipireno; Seso Sulijaya Suyono; Edy Purwanto; Budi Santoso; Edward Kurnia Setiawan Limijadi (Universitas Nahdlatul Ulama Surabaya, 2021)
The examination of sperm concentration in the laboratory is the calculation of the number and motility using a microscope or using a device. There are still some clinicians who doubt the accuracy of the sperm count results using a semen analyzer rather than using the manual method. This study aims is to determine the differences of the sperm concentration examination between the manual method and the automatic method. Subjects in this study were patients who carried out semen analysis tests at the Clinical Pathology Laboratory of RSIA